Primary retroperitoneal mucinous cystadenocarcinoma: a rare surgico-pathological entity - K., Sangeetha; Patel, Shilpa M.; Arora, Ruchi S.; Shah, Mona N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Ovarian cancer (OC) is the seventh most common cancer for females in the world. Epithelial OC is the most predominant pathologic subtype (85%-90%), with five major histotypes- serous, mucinous, endometrioid, brenner and clear cell tumour. Each have three pathological subtypes ie benign, borderline and malignant. Mucinous cystadenomas and carcinomas of the ovary are well-established and common tumors. Primary retroperitoneal mucinous cystadenomas and carcinomas are being very rare and histopathogenesis of which is still uncertain. Most pathologists suggest their origin through mucinous metaplasia in a pre-existing mesothelium-lined cyst. An accurate preoperative diagnosis of these tumors is challenging due to lack of established effective diagnostic measures. Hereby presenting a 50-year-old woman, who visited to the hospital with abdominal distension and discomfort since two months. Sonography and computed tomography scans were performed and showed large predominantly cystic lesion arising from right adnexa. Patient underwent exploratory laparotomy for removal of the tumor. Histology and immunohistochemistry revealed primary retroperitoneal mucinous cystadenocarcinoma.